2017
DOI: 10.4103/0019-5413.201709
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric analysis of the hip joint in South Indian population using computed tomography

Abstract: Background:Proximal femur has a significant functional modification on erect bipedal posture. Various proximal femoral parameters were analyzed in Western literature. This information was utilized in prosthetic designing. Implants designed for Western people are used in Indian patients undergoing hip surgeries such as internal fixation and replacement arthroplasty.Materials and Methods:The study was done among 200 individuals (400 hips) with a normal hip joint after ethical committee clearance. Computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 21 publications
6
31
3
6
Order By: Relevance
“…We observed a higher neck shaft angle in both groups, which were in contrast to that noted by Siwach et al 13 . Our findings, however, were comparable to those reported by Sengodan et al 17 , Deshmukh et al 18 and Saikia et al 19 wherein they reported higher neck shaft angles for the south, west and north-eastern Indian population, respectively. Anderson et al 20 studied inter-populational variation in human femoral neck shaft angles across 30 modern, historic and prehistoric human population samples and concluded that urban population have a higher neck shaft angle as compared to the non-mechanised rural population.…”
Section: Discussionsupporting
confidence: 89%
“…We observed a higher neck shaft angle in both groups, which were in contrast to that noted by Siwach et al 13 . Our findings, however, were comparable to those reported by Sengodan et al 17 , Deshmukh et al 18 and Saikia et al 19 wherein they reported higher neck shaft angles for the south, west and north-eastern Indian population, respectively. Anderson et al 20 studied inter-populational variation in human femoral neck shaft angles across 30 modern, historic and prehistoric human population samples and concluded that urban population have a higher neck shaft angle as compared to the non-mechanised rural population.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies analyzed the proximal femoral morphology using different specimens and methods of measuring [ 10 , 11 ]. We decided to analyze conventional radiographies since they are used as a standard in pre-operative planning for total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Detallar estas variantes en una población local asintomática, fundamenta la comprensión de los parámetros normales acetabulares y distingue patologías de variables anatómicas normales (Vandenbussche et al, 2008). Aunque este rango de normalidad pueda diferir según sexo y raza (Sengodan et al, 2017). El presente estudio intenta observar estos parámetros, en nuestra población.…”
Section: Discussionunclassified